The Evolution of ISIS In Indonesia With Regards to Its Social Media Strategy - Arifin, Naufal Armia (Parahyangan Center for International Studies, 2017)
AbstractISIS is a splinter terrorist group from Al-Qaeda that became a global threat in the last two decades. Its recruitment method that is different from its predecessor, also how it utilizes social media effectively, made them able to spread terror to every part of the world and conquer many territories of Iraq and Syria in order to fulfill their goal of a caliphate. However, recent development shows ISIS will lose their base of operation in both countries and there are signs of ISIS shifting their focus to Southeast Asia, with regards to the Marawi conquest. This paper aims to discuss how such development affects ISIS in Indonesia as the largest Muslim country in Southeast Asia and how the government responds to the situation.Â Keywords: isis; al-qaeda; social media; foreign fighters; indonesia.Â AbstrakISIS adalah kelompok teroris pecahan dari Al-Qaeda yang menjadi ancaman global dalam hampir dua dekade terakhir. Metode perekrutan anggota ISIS yang berbeda dari pendahulunya, serta bagaimana ISIS memanfaatkan sosial media dengan efektif membuat kelompok ini dapat menyebarkan teror di seluruh dunia dan menguasai banyak wilayah di Irak dan Suriah untuk memenuhi tujuan negara kekhalifahan mereka. Namun, perkembangan terkini menunjukkan ISIS akan kehilangan basis operasinya di kedua negara tersebut dan terdapat tanda bahwa ISIS akan mengalihkan fokus mereka ke Asia Tenggara dengan berkaca pada peristiwa penaklukan Marawi. Tulisan ini bertujuan untuk mendiskusikan bagaimana perkembangan tersebut berpengaruh pada ISIS di Indonesia sebagai negara Muslim terbesar di Asia Tenggara dan bagaimana pemerintah meresponnya. Kata Kunci: isis; al-qaeda; media sosial; pejuang asing; indonesia.